New triple oxygen isotope data of bulk and separated fractions from SNC meteorites: Evidence for mantle homogeneity of Mars. (17th April 2016) - Ali, Arshad; Jabeen, Iffat; Gregory, David; Verish, Robert; Banerjee, Neil R.
Abstract: We report precise triple oxygen isotope data of bulk materials and separated fractions of several Shergotty–Nakhla–Chassigny (SNC) meteorites using enhanced laser‐assisted fluorination technique. This study shows that SNCs have remarkably identical Δ 17 O and a narrow range in δ 18 O values suggesting that these meteorites have assimilated negligibly small surface materials (<5%), which is undetectable in the oxygen isotope compositions reported here. Also, fractionation factors in coexisting silicate mineral pairs (px‐ol and mask‐ol) further demonstrate isotopic equilibrium at magmatic temperatures. We present a mass‐dependent fractionation line for bulk materials with a slope of 0.526 ± 0.016 (1SE) comparable to the slope obtained in an earlier study (0.526 ± 0.013; Franchi et al. 1999). We also present a new Martian fractionation line for SNCs constructed from separated fractions (i.e., pyroxene, olivine, and maskelynite) with a slope of 0.532 ± 0.009 (1SE). The identical fractionation lines run above and parallel to our terrestrial fractionation line with Δ 17 O = 0.318 ± 0.016‰ (SD) for bulk materials and 0.316 ± 0.009‰ (SD) for separated fractions. The conformity in slopes and Δ 17 O between bulk materials and separated fractions confirm oxygen isotope homogeneity in the Martian mantle though recent studies suggest that the Martian lithosphere may potentially have multiple oxygen isotope reservoirs.